Upaya Penanggulangan Tindak Pidana Terorisme Dalam Perspektif Kriminologi - Nahdhodin, Muhammad; Sudarmanto, Kukuh; Triwati, Ani; Arifin, Zaenal (Universitas Semarang, 2024)
The study aims to examine attempts to counter-terrorism from a criminological perspective. This research is important given that terrorist crime is a global threat that affects countries and communities, with potentially negative effects, both physically and psychologically. The novelty of this research is in an attempt to counteract terrorist crime with a criminological perspective that uses local